Perancangan Sistem Informasi Pengendalian Intern Persediaan Barang Dagang Dengan Metode Reorder Point(Rop) - Laksamana Rajendra Haidar Azani Fajri; Teguh Setiadi; Moh. Muthohir (Seminar Nasional Teknologi dan Multidisiplin Ilmu (SEMNASTEKMU), 2023)
This research discusses the development and implementation of a Reorder Point (ROP) information system in the context of inventory management. ROP is a critical method for optimizing merchandise inventory, avoiding stock shortages, and minimizing inventory costs. The aim of this research is to design and implement an information system that allows companies to calculate and monitor ROP efficiently. The research methodology includes user needs analysis, software development, and system testing in real environments. The research results show that the ROP information system can help companies improve inventory control accuracy, reduce costs, and improve customer service. This research also identifies challenges in implementing ROP information systems and provides insight into how to overcome these obstacles. In an era of competitive business, the ability to respond quickly to changes in demand and delivery is the key to success. A sophisticated Reorder Point information system gives companies a competitive advantage by optimizing inventory levels and avoiding excess or shortage of stock that can be detrimental to the company. Additionally, by integrating data from various aspects of supply chain management, the system provides better visibility into company operations, enabling more timely decisions and accurate information. Therefore, the results of this study indicate that the ROP information system is a valuable asset in efficient inventory management and helps companies to remain relevant and sustainable in a dynamic business environment. In conclusion, ROP information systems are a valuable tool in efficient inventory management and contribute to the success of a company's supply chain.